2019
DOI: 10.3390/molecules24071201
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Death and Osteoblast Metabolic Activity Correlated to Hydrothermally Synthesised TiO2 Surface Properties

Abstract: Orthopaedic surgery comes with an inherent risk of bacterial infection, prolonged antibiotic therapy and revision surgery. Recent research has focused on nanostructured surfaces to improve the bactericidal and osseointegrational properties of implants. However, an understanding of the mechanical properties of bactericidal materials is lacking. In this work, the surface properties of hydrothermal TiO2 nanostructured surfaces are investigated for their effect on bactericidal efficiency and cellular metabolic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 54 publications
3
55
0
Order By: Relevance
“…We have recently shown that surfaces with nanoscale topography can significantly reduce respiratory syncytial virus and rhinovirus [77]. We have also shown that a range of nanostructured surfaces such as titanium and aluminium kill bacterial cells [78][79][80][81][82][83][84]. It is believed that such nanoscale surfaces will also be able to inactivate the SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that surfaces with nanoscale topography can significantly reduce respiratory syncytial virus and rhinovirus [77]. We have also shown that a range of nanostructured surfaces such as titanium and aluminium kill bacterial cells [78][79][80][81][82][83][84]. It is believed that such nanoscale surfaces will also be able to inactivate the SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…Later, a thorough examination of the surface, mechanical and wettability properties of multifunctional hydrothermally synthesised nanostructured materials were found to be capable of killing bacteria whilst improving osteoblast metabolic rates, leading to improved osseointegration and antibacterial properties of orthopaedic implants (Fig. 4(C)) [3]. Further to this, the mechanical properties, surface morphology, and stability of the TiO2 surface as a function of NaOH concentration were observed.…”
Section: Efforts For Promotion Of Biomedical Researchmentioning
confidence: 89%
“…Nano-pillared titanium [1][2][3][4] substrates have been fabricated using hydrothermal processing. The surface architecture has been selectively modulated using the fabrication processing parameters such as temperature, reaction time, and reactant molarity.…”
Section: Antipathogenic Surfaces That Kill Bacteria and Virusesmentioning
confidence: 99%
“…However, micro/ nano-topography of the surfaces of MNSS have shown to be most critical in determining the BE. 26,31,33,36,39,[44][45][46][47] In addition, BE has been reported to be inuenced by a number of other parameters such as the type of medium used for bacterial cell incubation, 48 bacterial inoculum concentration, 49,50 incubation time, 39,45,51,52 strain of bacteria. 26,45,53 Despite the popular belief that micro/nanoscale topographies are more effective against Gram-negative strains, numerous studies have also reported higher or equivalent BE of MNSS against Gram-positive strains.…”
Section: Factors Affecting Bactericidal Property Of Mnssmentioning
confidence: 99%
“…26,45,53 Despite the popular belief that micro/nanoscale topographies are more effective against Gram-negative strains, numerous studies have also reported higher or equivalent BE of MNSS against Gram-positive strains. 26,[36][37][38][39]51,54 For example, in a study, Jaggessar et al, fabricated six different TiO 2 nanopillars on titanium substrates and studied their bactericidal effect against both Gram-negative (Pseudomonas aeruginosa) and Gram-positive (Staphylococcus aureus) bacteria. 36 All six surfaces tested for bacterial viability, which showed a higher bactericidal rate on Gram-positive than on Gram-negative strains.…”
Section: Factors Affecting Bactericidal Property Of Mnssmentioning
confidence: 99%